The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fimmu.2022.843355
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Mechanical and Immunological Profiles of Polymeric Microneedles to Enable Vaccine and Immunotherapy Applications

Abstract: Biomaterials hold great promise for vaccines and immunotherapy. One emerging biomaterials technology is microneedle (MNs) delivery. MNs are arrays of micrometer-sized needles that are painless and efficiently deliver cargo to the specialized immunological niche of the skin. MNs typically do not require cold storage and eliminate medical sharps. Nearly all materials exhibit intrinsic properties that can bias immune responses toward either pro-immune or inhibitory effects. Thus, because MNs are fabricated from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Microneedles are a highly modular platform that can be engineered to deliver cargo via surface coating, soluble release, or controlled degradation. [117][118][119][120] In one preliminary study looking at the uptake of pro-insulin, coated stainless steel microneedle delivery was shown to elicit greater antigen-specific activation of cells compared to intradermal injection due to the sustained release from the needles. [121] In a separate study, insoluble T1D autoantigen was conjugated to naturally suppressive gold NPs (Figure 6D), and actively injected into the skin with microneedles.…”
Section: Materials Enable Direct Targeting Of Skin-resident Immune Ce...mentioning
confidence: 99%
“…Microneedles are a highly modular platform that can be engineered to deliver cargo via surface coating, soluble release, or controlled degradation. [117][118][119][120] In one preliminary study looking at the uptake of pro-insulin, coated stainless steel microneedle delivery was shown to elicit greater antigen-specific activation of cells compared to intradermal injection due to the sustained release from the needles. [121] In a separate study, insoluble T1D autoantigen was conjugated to naturally suppressive gold NPs (Figure 6D), and actively injected into the skin with microneedles.…”
Section: Materials Enable Direct Targeting Of Skin-resident Immune Ce...mentioning
confidence: 99%
“…From an immunology perspective, MNs led to similar activation of DCs and did not limit the ability to engage with antigen. [138] Coated stainless steel MNs have also been designed as ID delivery devices for ASITs. In preclinical T1D, stainless steel MNs coated with proinsulin delivered %86% of the therapy into local issue of a NOD mouse model (Figure 5A).…”
Section: Mns Deliver Antigen and Immunomodulatory Cues To Skin-reside...mentioning
confidence: 99%
“…designed a library of polymeric MNs consisting of polymers derived from the extracellular matrix, naturally derived polymers, and synthetic polymers. [ 138 ] Mechanical testing revealed varying stiffness and fracture forces for the MN arrays, with majority of the MNs being able to surpass a minimum fracture force of 4 N, required to penetrate skin. From an immunology perspective, MNs led to similar activation of DCs and did not limit the ability to engage with antigen.…”
Section: Biomaterials Circumvent Various Disadvantages Associated Wit...mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has the advantages of delivering a higher density of tolerizing immune signals per mass of administered materials as well as eliminating potentially immunostimulatory effects of the carrier material itself. [59,60] Wilson et al demonstrated carrierfree liver targeting by modifying protein and peptide antigens with polymeric forms of N-acetylgalactosamine (GalNAc) or Nacetylglucosamine (GluNAc), which enable them to bind to Ctype lectins on Kupffer cells, LSECs, and hepatocytes. [53] The authors found that 3 hours after IV administration, synthetically glycosylated ovalbumin (OVA) accumulated in the liver at a 2-fold higher level compared to un-glycosylated OVA.…”
Section: Livermentioning
confidence: 99%